Effect of Anode Thickness on Polarization Resistance for Metal-Supported Microtubular Solid Oxide Fuel Cells. Issue 4 (27th January 2017) - Sumi, Hirofumi; Shimada, Hiroyuki; Yamaguchi, Yuki; Yamaguchi, Toshiaki
Abstract : An anode functional layer (AFL) is inserted between anode substrate and electrolyte thin-film to increase the triple phase boundary (TPB) for anode-supported solid oxide fuel cells (SOFCs). On the other hand, better mechanical robustness, redox tolerance, rapid thermal cycling and cost reduction are expected for metal-supported SOFCs. The anode thickness of metal-supported cells (MSCs) is more important than the AFL thickness of anode-supported cells (ASCs), since the metallic substrate does not have TPB. In the present work, the metal-supported microtubular SOFCs with La0.6 Sr0.4 Co0.2 Fe0.8 O3 (LSCF)-(Ce0.9 Gd0.1 )O1.95 (GDC) cathode, GDC electrolyte, BaCe0.8 Y0.2 O3-δ (BCY) blocking layer and Ni-GDC anode on Ni substrate were investigated. The significant decrease in polarization resistance with increasing the anode thickness from 10 to 16 μm was confirmed by the distribution of relaxation times (DRT) analysis for the metal-supported microtubular SOFCs operated at 550°C.